Gender and Infrastructure in the World Bank. (2nd July 2015) - Ferguson, Lucy; Harman, Sophie
<x xml:space="preserve">Abstract</x> This article conducts a critical analysis of the World Bank's current infrastructure strategy from a feminist perspective, arguing that failures to define gender and set meaningful targets and indicators have meant that gender has not been integrated into the implementation of infrastructure projects. It sets out three limitations to the Bank's approach to gender and infrastructure: lack of awareness of gender in the four sectors that comprise infrastructure; the Bank's narrow approach to gender equality and women's empowerment; and the failure of the Bank to mainstream gender in its current infrastructure strategy.